Analysis and optimization of nozzle distance during turning of EN-31 steel using minimum quantity lubrication. (2022) - Kumar, Ajay; Singh, Gurpreet; Aggarwal, Vivek
Highlights: Experimental investigation into machining of EN-31 steel in different cooling conditions. Measure of cutting temperature using thermocouple installed in hole drilled on insert. Impact of MQL Nozzle distance on cutting temperature. Optimization of machining parameters using ANOVA. Investigation into the impact of nozzle distance utilizing ANOVA. Abstract: Traditional high volume cutting fluid is normally applied during manufacturing of product at shop floor to minimize severity of friction, wear, temperature and machining forces. It impacts the manufacturing performance if, the choice, application, handling and disposal of cutting fluid properly designed. Contrary to this, higher volume flow rate of metal working fluids applied in flood lubrication would adversely affects the environment, machine, materials, human and costly too. Hence, for ensuring the economy and ecology of machining process the high discharge rate of cutting fluids should be minimized. Therefore, machining should be conducted in such conditions where the aforementioned limitation should be avoided i.e. dry and minimum quantity lubrication. However, dry machining has limitation at higher levels of input variables so becomes unsuitable for mass production of difficult to cut materials. Therefore, in present investigations the minimum quantity lubrication of vegetable based oil has been utilized for investigating its impact the cutting temperature at different nozzle distances. The outcomes of changing the nozzle gap on temperature during turning of EN-31 Steel have been analyzed with ANOVA. The investigation results suggested that cutting speed has greater influence (68.44%) on temperature along with nozzle distance (30.75%).